Reduced 8-Gray Compared to Standard 12-Gray Total Body Irradiation for Allogeneic Transplantation in First Remission Acute Lymphoblastic Leukemia: A Study of the Acute Leukemia Working Party of the EBMT. Issue 1 (9th January 2023) - Spyridonidis, Alexandros; Labopin, Myriam; Savani, Bipin; Giebel, Sebastian; Bug, Gesine; Schönland, Stefan; Kröger, Nicolaus; Stelljes, Matthias; Schroeder, Thomas; McDonald, Andrew; Blau, Igor-Wolfgang; Bornhäuser, Martin; et al.
Abstract : In this registry-based study, we compared outcomes of allogeneic hematopoietic cell transplantation (allo-HCT) in adult patients with acute lymphoblastic leukemia (ALL) transplanted in first complete remission (CR-1), following conditioning with total body irradiation (TBI) at a standard 12-Gray or at a lower 8-Gray total dose. Patients received fludarabine (flu) as the sole chemotherapy complementing TBI. Eight-Gray TBI/flu was used in 494 patients and 12-Gray TBI/flu in 145 patients. Eighty-eight (23.1%) and 36 (29%) of the patients had Ph-negative B-ALL, 222 (58.3%) and 53 (42.7%) had Ph-positive B-ALL, 71 (18.6%) and 35 (28.2%) T-ALL, respectively ( P = 0.008). Patients treated with 8-Gray were older than ones received 12-Gray (median 55.7 versus 40.3 years, P < 0.0001) and were more frequently administered in vivo T-cell depletion (71% versus 40%, P <0.0001). In a multivariate model adjusted for age, type of ALL, and other prognostic factors, leukemia-free survival (primary endpoint) as well as relapse, nonrelapse mortality, overall survival, and GVHD-free, relapse-free survival were not influenced by the TBI dose. These results were confirmed when we focused on patients <55 years of age (median 47 years). Patients with Ph-positive ALL or T-ALL had significantly better survival outcomes than ones with Ph-negative B-ALL, mainly due to significantly fewer relapses. We conclude that 8-Gray TBI is sufficient for adult patients with ALL transplanted in CR-1 with no additional benefit of augmenting the conditioning intensity to 12-Gray.